From numbers to forms. ﻿The digital turn in morphogenic processes - Michela Barosio; Rossella Gugliotta (Agathón)
The digital turn, or specifically the second Digital Turn, was at disposal of the architectural and urban project sophisticated morphogenic tools. These tools have been used mainly to create new forms with non-Euclidean geometries and their integration with building systems, also dynamic. This paper investigates the possibility of using parametric tools to handle urban transformations based on formal parameters and not merely quantitative ones, coming from the morphological analysis of the existent city. To this purpose, three tools have been identified and analysed (type, diagram and model), to translate the morphologic urban characteristics in elements embeddable into parametric processes, investigating their potential and possible limits also with two practical experimentations.